The role of family as a means of moral value formation: a review of moral values education in the family environment - Sulistyarini Sulistyarini; Daniel Daniel; Indra Gunawan (Sean Institute, 2024)
The purpose of this article is to examine the family as a means of formation in instilling moral value education for children or adolescents. The family has an important role in moral value education for children. This role is increasingly important in the era of globalization and modernization which continues to have an impact on children's behavior, where in the current era, children or adolescents experience moral degradation. The method used in examining this topic is to use a literature study by collecting various literature related to the family and the study of moral value education. The results and discussion are that families need to create an environment that supports children's moral development in the long run. The cultivation of moral values to children must start early. Parents need to be good role models for children and provide open communication. Parents also need to involve children in family activities so that moral values can be integrated into children's daily lives. By implementing these strategies, families can play a more active role in educating children to become moral, responsible and ethical people.